215k views
2 votes
5a-6-2a=12 solve and check

User Patros
by
6.0k points

2 Answers

3 votes
5a-6-2a=12
3a-6=12
3a=12+6
3a=18 (isolate variable)
18 divided my 3 is 6
a=6
User Sebrock
by
6.0k points
1 vote

Answer:

a = 6

Subtract 2a from 5 a .

3 a − 6 = 12

Move all terms not containing a to the right side of the equation.

Add 6 to both sides of the equation.

3 a = 12 + 6

Add 12 and 6 .

3 a = 18

Divide each term by 3 and simplify.

Divide each term in 3 a = 18 by 3 .

3 a/ 3 = 18 /3

Reduce the expression by cancelling the common factors.

Cancel the common factor.

(3 a /3) *gone* = 18/ 3

Divide a by 1 .

a = 18/ 3

Divide 18 by 3 .

a = 6

HOPE THIS HELPED!!!!!!!!!!!!!XDDDDDDDDDD

User Robber Pen
by
5.4k points